Correcting scan‐to‐scan response variability for a radiochromic film‐based reference dosimetry system. Issue 10 (9th September 2015) - Lewis, David; Devic, Slobodan
Abstract : Purpose: In radiochromic film dosimetry systems, measurements are usually obtained from film images acquired on a CCD‐based flatbed scanner. The authors investigated factors affecting scan‐to‐scan response variability leading to increased dose measurement uncertainty. Methods: The authors used flatbed document scanners to repetitively scan EBT3 radiochromic films exposed to doses 0–1000 cGy, together with three neutral density filters and three blue optical filters. Scanning was performed under two conditions: scanner lid closed and scanner lid opened/closed between scans. The authors also placed a scanner in a cold room at 9 °C and later in a room at 22 °C and scanned EBT3 films to explore temperature effects. Finally, the authors investigated the effect of altering the distance between the film and the scanner's light source. Results: Using a measurement protocol to isolate the contribution of the CCD and electronic circuitry of the scanners, the authors found that the standard deviation of response measurements for the EBT3 film model was about 0.17% for one scanner and 0.09% for the second. When the lid of the first scanner was opened and closed between scans, the average scan‐to‐scan difference of responses increased from 0.12% to 0.27%. Increasing the sample temperature during scanning changed the RGB response values by about −0.17, −0.14, and −0.05%/°C, respectively. Reducing the film‐to‐light source distance increased the RBG response values about 1.1, 1.3, and 1.4%/mm, respectively. The authors observed that films and film samples were often not flat with some areas up to 8 mm away from the scanner's glass window. Conclusions: In the absence of measures to deal with the response irregularities, each factor the authors investigated could lead to dose uncertainty >2%. Those factors related to the film‐to‐light source distance could be particularly impactful since the authors observed many instances where the curl of film samples had the potential to cause dose uncertainty in excess of 5%. Two expedients will eliminate the uncertainties: a transparent sheet (preferably glass) placed over the scanned film keeps the film‐to‐light source distance constant, and an EBT3 reference film included in all scans provides correction factors for measured response values.